Exploring Human Interaction in Virtual Reality: An Experience Report on Users with and without Visual Impairment - Fernandes, Paula C.; Rocha, Gabriel Henrique M.; Adachi, Bruno H.; Silvas, Flávia P. C.; Coelho, Bruno N.; Delabrida, Saul (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Virtual reality (VR) offers diverse applications across various areas and purposes, yet understanding inclusive and accessible environments for persons with disability (PwD) remains incomplete. Creating scenarios with users of varying interaction abilities is essential to promote equity in virtual environments and ensure inclusive, comprehensive design solutions. Specifically, enabling a level playing field for persons with low vision presents significant challenges, as visual feedback is a primary mode of interaction. This experience report describes the human interaction and user studies involving sixteen volunteers, including nine individuals without disabilities and seven with low vision, within VR environments. The research investigates how VR can be leveraged as a tool for inclusion, creating spaces that are more integrative for PwD. It highlights the necessity of adapting these virtual spaces through tailored approaches that meet the unique needs of persons with visual impairment. The preparation and experimentation emphasize the importance of understanding and anticipating interaction dynamics in VR to effectively include PwD in the technology. Additionally, the study considers alternative feedback, design considerations, and other interaction interfaces to enhance inclusion. The paper discusses the experiences, challenges, and shared insights, aiming to guide future user tests and address VR interactions for individuals with low vision.